Antibiotic use on Kenya’s dairy farms is putting consumers and animals at risk - Muloi, Dishon M.; Moodley, Arshnee (2024)
Farmers often use antibiotics to keep their livestock healthy. They’re sometimes used as “quick fixes”, to avoid more costly management measures like regular disinfection, waste management, routine vaccination or provision of clean drinking water.